Changes of refractive status after pterygium surgery in a tertiary eye hospital in Bangladesh - Khaja, M. Kamruzzaman; Mujtaba, Mahmood; Islam, Khairul; Afroze, Rokhsana; Huq, Sajidul (International Journal of Research in Medical Sciences, 2022)
Background: The aim of this study was to determine the amount of refractive changes after pterygium surgery and to compare the relationship between amounts of astigmatism with grade of pterygium. Methods: A prospective, interventional, comparative study was conducted on one hundred eyes of 100 patients of primary pterygium attending the outpatients department of Ispahani Islamia eye hospital and Institute, Dhaka from May, 2019 to November, 2019. Pterygium was graded according to morphology and the extent of corneal encroachment. Manifest refraction was performed preoperatively and at 1, 3 and 6 months postoperatively. All patients underwent stem cell conjunctival autograft by fibrin glue by different surgeons. Results: The astigmatism decreased significantly following pterygium excision. The mean pre-operative astigmatism was 1.69±1.13 D and reduced post-operatively to 0.23±0.27 D (p value <0.001). The mean pre-operative VA was 6/24 and reduced post-operatively to 6/9. Conclusions:There was statistically significant correlation between grade of pterygium and induced astigmatism (p value <0.001). The present study verifies that amount of pterygium induced astigmatism is directly proportional to increase in the size of pterygium.